Acute and sub-acute toxicity of a lyophilised aqueous extract of the aerial part of Spilanthes africana Delile in rats. (22nd August 2015) - Ngueguim, Tsofack Florence; Djouwoug Noussi, Clarice; Donfack, Jean Hubert; Gounoue, Kamkumo Raceline; Mbatchou, Adolphe; Kamtchouing, Pierre; Dimo, Theophile
Abstract: Ethnopharmacological relevance: Spilanthes africana is a plant used in several countries for the treatment of toothache, malaria, fracture, pneumonia, and dysentery. In order to establish the safety of aerial part of the plant extract, the acute and sub-acute toxicity of the aqueous extract of this plant has been evaluated in male and female young rats. Material and methods: In acute toxicity, the effects of a single oral dose (2000 mg/kg and 5000 mg/kg) of the lyophilised aqueous extract have been determined. General behaviour, adverse effects and mortality were determined for up to 14 days. In sub-acute treatment, the effects of the extract in daily single oral administration at the doses of 250, 500 and 1000 mg/kg during 28 days were evaluated. One group treated at the dose of 1000 mg/kg for 28 days was let without treatment during 14 days to assess the possible reversibility of the harmful effects of the extract. Body weight, food and water intakes, biochemical and haematological parameters were recorded. Histopathological examination of liver, kidney and lungs were assessed. Results: In acute study, a single administration of the aqueous extract at the doses of 2000 mg/kg or 5000 mg/kg did not induce mortality. Thus, the LD50 of the aqueous extract of S. africana has been estimated higher than 5000 mg/kg. Four hours after administration of the extract, a reduction of the mobility, sensitivity to the noise and to touch has been observed. In sub-acute study, the administration of the extract during 28 days at all doses did not significantly modify the body weight. On the haematological analysis, a decrease of the rate of monocytes and a rise of lymphocytes counts were observed among the male group. In both sexes, it appeared a decrease of the rate of granulocytes two weeks after stopping the treatment. It has also been observed in different groups among the females, an increase of the mean corpuscular content and the mean concentration in haemoglobin as well as an increase of platelets. A significant decrease of transaminases, alkaline phosphatase, triglycerides, and a significant increase of total bilirubin compared to the normal group has been observed. There was a significant decrease in renal catalase in both sexes compared with different control groups. Besides, a significant increase of the kidney rates of glutathione and malondialdehyde have also been observed in the female treated at the doses of 1000 mg/kg. Histopathological analysis has shown vascular congestion and leucocyte infiltrations in the liver of animals treated at the dose of 1000 mg/kg. This congestion has been marked in satellite group. In the kidney female satellite group, tubular clarifications have been observed and disappear when stopping the treatment. Conclusion: These results show that the aqueous extract of S. africana given by the oral route is slightly toxic. However in sub-acute treatment, higher doses could provoke functional and structural changes in the organism which could in part reversible. Thus the extract should be used with caution. Graphical Abstract: